HUBUNGAN KECANDUAN GAME ONLINE TERHADAP INTERAKSI SOSIAL PADA REMAJA DIKELURAHAN CIPEDAK JAKARTA SELATAN - Ananda Oktavianti (2020)
Online gaming addiction is already set up by the World Health Organization (WHO) as the International Statistical Classification of Diesease (ICD) which is classified as a mental disorder disease. The negative impact of online gaming is to make users cool down with their busy life and reduce social interactions. The purpose of this research is to know the relationship between online gaming addiction with social interactions. This type of research used Crossectional with Accidental Sampling method with a sample number of 112 teenagers in South Jakarta Cipedak village. The instruments used were Game Addiction Scale (GAS) and Social Skills Inventory (SSI). Data analysis using the Chi-Square test. The results showed there was a link between online gaming addiction with social interaction (p value = 0.004). Suggestions for teenagers to reduce game play and find new more rewarding hobbies, for researchers further add factors that can affect the addiction of online gaming, to educational instutions to add material about online gaming addiction.